Development of nanoscale screening technology for the detection and quantification of aggregation in protein therapeutics - Lone, Mudasir (2013)
The use of proteins as therapeutics is one of the fastest growing sectors of the pharmaceutical industry, particularly monoclonal antibodies. However, a significant challenge in the development of such protein-based medicines is to counter aggregation of the proteins in solution (as these drugs are typically administered by injection). In solution form, aggregation of the normally monomeric protein ingredient affects therapeutic efficiency and reduces shelf life. Moreover, the rapid formation of aggregates in patients during the administration of therapeutic proteins can lead to immunological reactions which could be fatal. Hence, the long term storage of proteins in solution is discouraged. Lyophilization (vacuum drying) is considered to be an effective route for ensuring longer shelf life and better stability of protein therapeutics. However, aggregation can still occur, because the driving forces for aggregation (covalent as well as non-covalent interactions such as hydrogen bonds, van der Waals forces and hydrophobic interactions) are influenced by lyophilization induced changes in the pH, temperature, exposure to interfaces, and dehydration stress. Lyoprotectants such as sugars can counter the undesirable consequences of lyophilization depending upon their nature and potential. Several mechanisms have been proposed for the role of the lyoprotectants. The comprehensive investigation into the inherent nature and influence of lyoprotectants on a protein therapeutic during lyophilization is hence important. In this project an attempt has been made to develop a novel nanoscale screening methodology for the detection, quantification, characterization and prevention of protein aggregation. Initially, ferritin and then a polyclonal IgG (antiglucose-6-phospate dehydrogenase antibody) antibody have been used as model proteins for these studies. The effect of lyophilization on the level of aggregation of IgG was studied and compared to reports in the literature. IgG was exposed to seven cycles of lyophilization, where each cycle of lyophilization was followed by reconstitution and characterization. IgG was also lyophilized with different excipients (sucrose and mannitol, alone and in combination) in different molar ratios. In the liquid state, the formulations were characterized on the basis of particle size and antigen binding activity, whereas in the dry powdered form, the formulations were characterized by studying morphology, thermal stability, and secondary structural alterations in order to establish a relationship amongst the indicated properties. Atomic force microscopy (AFM), dynamic light scattering (DLS) and single particle tracking (Nanosight) were used to study particle size. The identification of different components at the nanoscale and general morphology were screened by AFM and scanning electron microscopy (SEM). Subsequently, the thermal properties and structural alterations respectively were analysed by differential scanning calorimetry (DSC) and infra read spectroscopy (ATR-FTIR) spectroscopy. The antigen binding activity was investigated by performing an indirect ELISA assay on the lyophilized formulations. Lyophilization of ferritin and IgG caused a significant decrease in the proportion of monomeric species was confirmed by AFM, DLS and Nanosight. Dimeric, lower-multimeric and larger aggregates existed in variable proportions for both ferritin and IgG. Powdered lyophilized ferritin formulations showed aggregation, increased crystallinity (concomitant decrease in amorphicity), porosity and flakiness which in case of IgG increased with repeated lyophilization. A consistent increase in the extent of aggregation (unfolding of Fabs and Fc) was detected by DSC and an increase in the beta-sheet structure coupled with structural re-arrangement within the components by ATR-FfIR. The presence of sucrose in IgG formulations resulted in reduced aggregation and enhanced porosity. The inclusion of Mannitol promoted crystallinity, decreased porosity when used alone, however, improved the efficiency of sucrose in combined formulations. The nature of crystals formed by mannitol during lyophilization was shown by SEM and confirmed by AFM. The data obtained from DLS, NTA, AFM, DSC,ATR, and SEM was consistent with by ELISA results which indicated a significant fall in IgG activity upon repeated lyophilization, and improvement in the activity when IgG was formulated with sucrose, which significantly enhanced in combination with mannitol. The benchmark provided by this work would serve as a precursor for developing a novel screening standard for optimizing and improving the therapeutic efficiency of other proteins besides furnishing a detailed account of the disparity in correlating the data from multiple novel techniques. The findings of our work can be directly translated to biotech and biopharm industries for the enhancement of protein based therapeutics.